IS THE BALKANIZATION OF THE UKRAINIAN-RUSSIAN CONFLICT PROBABLE? - A. P. Koshkin; V. V. Cherdantsev (Russian Journal of Economics and Law)
Objective: to determine the possibility and probability of Balkanization of the Ukrainian-Russian inter-societal relations.Methods: the need to study the main factors affecting the state of the modern Russian-Ukrainian conflict in its ethno-political dimension, with the predominat focus on intersocietal relations, determined the use of the historical-genetic, comparative-historical and typological methods of investigation, integrated with the systemic approach.Results: the main parallels are shown that occur when comparing the ethno-political situation in the Balkans and, above all, the Serbian-Croatian relations, with the current Russian-Ukrainian conflict, mainly at the level of relations of Russians and Ukrainians as ethnic groups. The ethno-social and ethno-political differences of the genesis and current state of both conflicts do not provide a sufficient basis for specific predictions about the inevitable Balkanization of the Russian-Ukrainian conflict.Scientific novelty: the article proves the inconsistency of unambiguous similes of the Russian-Ukrainian conflict and inter-ethnic Serbian-Croatian conflict at inter-societal and associated levels; it shows the significant differences of the conflict situations that do not lead to dogmatic conclusions about the development of the Russian-Ukrainian relations by the Yugoslavia scenario.Practical significance: the main provisions and conclusions of the article can be used in scientific and pedagogical activity in the study of ethnos and ethnicity, in the analysis of ethno-political processes in modern Ukraine and consideration of the status and prospects of the development of Russian-Ukrainian relations.